PENINGKATAN KEMAMPUAN PENGGUNAAN APLIKASI PEMBUKUAN BAGI UMKM - ERITA ROSALINA; Y YOKOTANI; S.SUHAIDAR (KRIDA CENDEKIA, 2022)
The current business era is experiencing very significant changes where technology plays an important role in production activities so that efficiency and cost-effectiveness occur. Companies in decision making or data retrieval can be done quickly when needed via the internet network. A good internet network can assist in the stages of the production process and bookkeeping so that it can be done at any time. MSMEs have many limitations in human resources or human resources, capital, and access to financial institutions, technology, management, marketing, and information. Limitations in the field of HR can cause losses for MSME actors, especially in making financial reports. This limitation should not be an obstacle for MSME business actors but should be a challenge to be faced. Regarding the problem of MSMEs which cannot make financial reports but have internet access, this can be a problem that can be solved by socializing the use of internet access to make financial reports. If MSME actors do not want to use the internet in making financial reports, it is not also a big problem. At this time there are bookkeeping applications that are offline but must first install the application on the Android phone.